Student to Students Interaction through Traditional Games in English Classroom. - Hermaniar, Yulieda; Palupi, Tri Winindyasari (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2018)
The study discusses the use of traditional games is English teaching which is considered important to promote learners-centered learning. Traditional games offer familiarities, fun, and create natural English environment which is not offered in studentsâ real environment in Indonesia, considered English as a foreign language. Therefore, the researcher is interested in carrying out the stages used in the teaching and learning process dealing with the stated topics. The observation and interview are conducted in Elite English Course Banjarmasin which uses games as the method in their classroom. The result of this study is under the discussion of what traditional games are used in 5 meetings, how the teaching stages are conducted, time allotment, teacherâs role, and how it promotes active studentsâ interaction.